The Impact of Social Media on New Vocabulary Adoption Among Indonesian Teenagers - Nuvi Nurul Afiah; Najhah Barnamij; Mubarok Fatahillah; Ni’amillah Aqiel Siroj; Nurul Husnaeni (Sekolah Tinggi Agama Islam Kuningan, 2026)
The purpose of this study is to explore the factors influencing the adoption of new vocabulary in the Indonesian language through social media. This research employs a quantitative approach with a sample of 400 respondents, focusing on Indonesian teenagers who are active users of various social media platforms. The object of the study is the usage of newly emerging vocabulary in the Indonesian language. Data were collected using a structured questionnaire distributed online via Google Forms. The collected data were analyzed using multiple linear regression with the assistance of SPSS version 27 software. The results show that the frequency of social media use, the incorporation of new vocabulary into daily conversations, and the use of slang have a significant effect on the frequency of new vocabulary adoption. In addition, the findings indicate that younger generations tend to be more open and inclined to adopt new linguistic trends emerging from social media. The coefficient of determination (R²) value of 0.42 demonstrates that the independent variables explain 42% of the variation in the adoption of new vocabulary in the Indonesian language, while the remaining percentage is influenced by other factors not examined in this study.